Relationship of polymorphism rs3800231 in FOXO3 gene and clinical severity with oxidative stress markers in sickle cell disease - Bernardo, Victoria Simões [UNESP] (2020)
Sickle cell disease (SCD) is a hereditary disease characterized by a clinical course highly variable that is significantly affected by several modifying factors, whose majority still poorly understood. Due to the importance of the chronic inflammatory and oxidative processes in the SCD pathophysiology, the understanding of the signaling pathways that control the reactive oxygen species (ROS) levels is one of the major fields that need research. Studies involving the genetic sequence of the Forkhead box O3 (FOXO3) suggest that this gene presents a promising target of new genetic markers related to SCD clinical severity. Therefore, the aim of this study was to investigate a possible influence of the FOXO3 polymorphism (c.35-2764A > G; rs3800231) in the FOXO3 gene on the clinical severity and on the oxidative status of SCD individuals. We evaluated 313 blood samples, 196 of SCD patients (SCD) and 117 of individuals without hemoglobinopathies (CG). FOXO3 polymorphism was identified by PCR-RFLP. Biochemical parameters were measured using spectrophotometric methods. Moreover, patients were classified into clinical categories (mild, intermediate, and severe), according to their severity scores previously calculated. We found higher genotypic and allelic frequencies of the wild form (A) of the allele of the SNP rs3800231 in patients with SCD (p < .01), regardless of clinical classification. We did not find any significant involvement of FOXO3 polymorphism in the clinical severity classification, as well as in the severity scores. On the other hand, the mutant allele (G) was related to higher catalase activity (p = .01), along with no alteration on oxidized biomolecule levels (p = .65). Thus, we concluded that SNP rs3800231 did not play a significant role as a direct modifying factor in the clinical severity of SCD but it may be involved in the modulation of the oxidative profile of this genetic disorder.